PERANAN AUDITOR INTERNAL DALAM UPAYA PENDETEKSIAN DAN PENCEGAHAN FRAUD TERHADAP PELAKSANAAN GOOD CORPORATE GOVERNANCE - Devi Anggriani; Juniati Gunawan (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2015)
Internal auditing serves help management in detection and prevention his that happens at an organization in the implementation of the good corporate governance. Principies of good corporate governance is an indicator the achievement of the balance interests, so the clash interests that occurs could focus and controlled and not result in losses to each party. According to previous studies, fraud led to the collapse of the world class companies. This is because inactive of mechanism good corporate governance. The -role of the auditors internal in an effort to detection and prevention his has a strong enough. And the role of the auditors internal also has a very important in good corporate governance. Methods used in this research is research methodology explanatory research with quantitative survei aims to understand the influence of the role of the auditors internal (components expertise, the scope of the work, the approach) that was undertaken auditor internal in order to detection and prevention his with the implementation of the good corporate governance on a 50 respondents is the company open a listing on the Bursa Efek Indonesia through the distribution of the questionnaire. The result has been concluded, the expertise, the scope of the work, the approach that was undertaken internal audit influential indirectly on the ,corporate governance through the intervening the detect and prevent offraud. For the company public, should be channeled to detect cheating through prevention, prevent is the root cause problems cheating that the creation of principles of good corporate governance in the company.